Perovskite phase AgCuF3: multiple Dirac cones, 100% spin polarization and its thermodynamic properties. Issue 3 (17th May 2019) - Kuang, Minquan; Li, Tingzhou; Cheng, Zhenxiang; Khachai, Houari; Khenata, R.; Yang, Tie; Lin, Tingting; Wang, Xiaotian
Abstract : This work focuses on a new phase material, AgCuF3, which has a combination of multiple Dirac cones and 100% spin polarization properties. Compared to the non‐spin polarization system LaCuO3, the spin‐polarized Dirac behavior in AgCuF3 is intrinsic and does not need the help of additional experimental conditions. Abstract : Very recently, experimentally synthesized phase LaCuO3 was studied by Zhang, Jiao, Kou, Liao & Du [ J. Mater. Chem. C (2018), 6, 6132–6137], and they found that this material exhibits multiple Dirac cones in its non‐spin‐polarized electronic structure. Motivated by this study, the focus here is on a new phase material, AgCuF3, which has a combination of multiple Dirac cones and 100% spin polarization properties. Compared to the non‐spin‐polarized system LaCuO3, the spin‐polarized Dirac behavior in AgCuF3 is intrinsic. The effects of on‐site Coulomb interaction, uniform strain and spin–orbit coupling were added to examine the stability of its multiple Dirac cones and half‐metallic behavior. Moreover, the thermodynamic properties under different temperatures and pressures were investigated, including the normalized volume, thermal volume expansion coefficient, heat capacity at constant volume and Debye temperature. The thermal stability and the phase stability of this material were also studied via ab initio molecular dynamic simulations and the formation energy of the material, respectively.